Carbon reserves in coffee agroforestry in the Peruvian Amazon - Vallejos Torres, Geomar (2024)
All claims expressed in this article are solely those of the authors and do not necessarily represent those of their affiliated organizations, or those of the publisher, the editors and the reviewers. Any product that may be evaluated in this article, or claim that may be made by its manufacturer, is not guaranteed or endorsed by the publisher.